Patient Rights Protection of tuberculosis (TB) Human Immunodeficiency Virus (HIV) on integrated Health Services National Health insurance in Semarang - Florentina Novitasia; Endang Wahyati Yustina; Suwandi Sawadi (SOEPRA, 2019)
Everyone has the right to JKN integrated health care including TB-HIV patients. This study aims to determine the regulation of the right to health care in TB-HIV patients, the implementation of protection of the rights to health care in TB-HIV patients and the factors that influence the implementation of protection of the rights to health care in TB-HIV patients. The research was conducted in Semarang City, throughout health care offices and health care institutions, as follows, the BPJS Office in Semarang City Branch, Semarang City Health Office, Kariadi Hospital, KMRT Wongsonegoro Hospital, Panti Wilasa Dr.Cipto Hospital, Lebdosari Health Center, Halmahera Health Center, Private Practice (DPM), NGO Peduli Kasih, NGO Aisyah and the AIDS Commission (KPA).This study used a sociological juridical approach with analytical descriptive specifications. The data used are primary data and secondary data through field studies and literature studies. The study used the purposive sampling /non-random sampling method. This study chose a population that includes TB-HIV patients in health care facilities in the city of Semarang. The method of presenting data is done in narrative form, tables, and charts. In this sociological approach study, whose data mainly is in narrative descriptions, the data analysis used is qualitative.The result of the study indicates that the regulation regarding health care services for TB-HIV patients has already existed for both in general and specifically. Protection of rights to JKN integrated health service for TB-HIV patients has been obtained. It can also be seen that the right to obtain the health services has been regulated and implemented however, the implementation of the right to health insurance for TB-HIV patients has not been regulated in legislation. Factors that influence are juridical, sociological and technical factors. The juridical factors that influence are the existence of regulations regarding TB and HIV however separately. Sociological factors that influence are the presence of stigma in the family, community and health workers. Furthermore, the technical factors are the absence of socialization to health workers regarding regulations and technical manuals related to TB-HIV.